Purine analogs inhibit nerve growth factor-promoted neurite outgrowth by sympathetic and sensory neurons - Greene, LA (J Neurosci, 1990)
Past studies have shown that purine analogs block certain, but not all, responses of cultured rat PC12 pheochromocytoma cells to nerve growth factor (NGF). In the present work, newborn rat sympathetic and sensory neurons were exposed to NGF in the presence or absence of the purine analogs 6-thioguanine and 2-aminopurine. These compounds reversibly suppressed NGF-dependent neurite outgrowth by the neurons and did so at concentrations comparable to those effective on PC12 cells. In contrast to their effects on neurites, neither compound significantly blocked NGF-promoted neuronal survival. Similar effects were seen with cultures of chick embryo sympathetic ganglia. These findings show that purine analog effects on NGF responses can be extended to mammalian and avian neurons. Moreover, the differential effects of the analogs on neurite outgrowth and survival indicate that these 2 actions of NGF can be dissected from one another and may represent different mechanistic pathways.